Validation of claims‐based algorithms for psoriatic arthritis - Lee, Hemin; Ford, Julia A.; Jin, Yinzhu; Cho, Soo‐Kyung; Santiago Ortiz, Adrian J.; Tong, Angela Y.; Kim, Seoyoung C. (Pharmacoepidemiology and drug safety, 2020)
Purpose An increasing number of new medications are being developed and approved for psoriatic arthritis (PsA). To generate real‐world evidence on comparative safety and effectiveness of these drugs, a claims‐based algorithm that can accurately identify PsA is greatly needed. Methods To identify patients with PsA, we developed seven claims‐based algorithms based on a combination of diagnosis codes and medication dispensing using the claims data from Medicare parts A/B/D linked to electronic medical records (2012‐2014). Two physicians independently conducted a chart review using the treating physician's diagnosis of PsA as the gold standard. We calculated the positive predictive value (PPV) and 95% confidence intervals of each algorithm. Results Of the total 2157 records identified by the seven algorithms, 45% of the records had relevant clinical data to determine the presence of PsA. The PPV of the algorithms ranged from 75.2% (algorithm 1: ≥2 diagnosis codes for PsA and ≥1 diagnosis code for psoriasis) to 88.6% (algorithm 7: ≥2 diagnosis codes for PsA with ≥1 code by rheumatologist and ≥1 dispensing for PsA medication). Having ≥2 diagnosis codes and ≥1 dispensing for PsA medications (algorithm 6) also had PPV of 82.4%. Conclusions All seven claims‐based algorithms demonstrated a moderately high PPV of 75% to 89% in identifying PsA. The use of ≥2 diagnosis codes plus ≥1 prescription claim for PsA appears to be a valid and efficient tool in identifying PsA patients in the claims data, while broader algorithms based on diagnoses without a prescription claim also have reasonably good PPVs.